Open Space Criteria for Residential Complexes Evaluation and implementation of urban housing standards - Tara Azad Rauof; Nahedh Taha Al-Qemaqchi (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Globally, urban pieces in the form of Residential Cities are rising in an enormous rate since the beginning of the 2000s. The spread of this new trend is mainly due to urban population growth and to manmade crisis. In Kurdistan region of Iraq, particularly since 2003, major housing shortages lead to the appearance of so many small residential communities (called villages) which were considered at the time as a quick solution to the problem. However, although these projects were designed and built by qualified companies, it remained to be questionable whether the planning and design criteria set by the State Commission of Housing have been implemented and if any of dweller’s feedback, whether positive or negative, have been evaluated. With respect to the question of “to what extend the designers of the residential projects took the urban housing standards of the ministry of construction of Iraq into consideration “this study is to focus on the criteria of open spaces ratio in three existing urban housing projects in Sulaimany city in Iraq by taking into account the hypothesis which state that there is a significant ignorance of such criteria in the existing and upcoming urban residential projects. The study adopts a methodology of direct comparison between the existing open areas ratio and the one required by the above mentioned planning and design criteria. The results show the residential projects have low level of implementation of the regulation, with comparatively small differences between the projects added to that is the fact that the inhabitants had low level of satisfaction